Evolution of Industrial Policy in Chile: Analysis of the Period 1990-2022 - Rodrigo Barra Novoa (FapUNIFESP (SciELO), 2024)
This study provides a comprehensive and critical analysis of the trajectory of industrial policy and technological absorption in Chile over the last three decades. The article examines the paradigm and institutional shift in the promotion of innovation, highlighting significant advances in key sectors of the Chilean economy, such as mining, salmon farming, fruit farming and the emerging green hydrogen sector. The research underlines the key role of the state in Chile's industrial and technological development, supported by institutions such as CORFO and ANID. Key factors driving this incremental progress include macroeconomic stability, investment in infrastructure, increased R&D funding and policies aimed at fostering innovation. However, to improve the effectiveness of the industrial strategy and address challenges related to regional inequality, a more adaptive and sustained approach is required to fully capitalise on the opportunities offered by the country's resources and capabilities.
Keywords: E02; O31; O32; P42; 330; Industrial Policy; Technology Absorption; Innovation; Economic Development